Anthrax Susceptibility: Human Genetic Polymorphisms Modulating ANTXR2 Expression - Zhang, Zhang; Zhang, Yan; Shi, Minglei; Ye, Bingyu; Shen, Wenlong; Li, Ping; Xing, Lingyue; Zhang, Xiaopeng; Hou, Lihua; Xu, Junjie; Zhao, Zhihu; Chen, Wei (Toxins, 2015)
Anthrax toxin causes anthrax pathogenesis and expression levels of ANTXR2 (anthrax toxin receptor 2) are strongly correlated with anthrax toxin susceptibility. Previous studies found that ANTXR2 transcript abundance varies considerably in individuals of different ethnic/geographical groups, but no eQTLs (expression quantitative trait loci) have been identified. By using 3C (chromatin conformation capture), CRISPR-mediated genomic deletion and dual-luciferase reporter assay, gene loci containing cis-regulatory elements of ANTXR2 were localized. Two SNPs (single nucleotide polymorphism) at the conserved CREB-binding motif, rs13140055 and rs80314910 in the promoter region of the gene, modulating ANTXR2 promoter activity were identified. Combining these two regulatory SNPs with a previously reported SNP, rs12647691, for the first time, a statistically significant correlation between human genetic variations and anthrax toxin sensitivity was observed. These findings further our understanding of human variability in ANTXR2 expression and anthrax toxin susceptibility.